Challenges to engage medical assistant students in 5E flipped learning environment - Bala Krishnian Muniandy; Por Fei Ping (Universitas Muhammadiyah Malang, 2023)
Flipped classroom approaches envision students using technology to access the lecture and other instructional resources outside of the classroom to engage them in active learning during class time. Although flipped classroom practices have been used in a number of educational studies and found positive outcomes, there were still some challenges with this approach. Therefore, there is a need for an innovative flipped classroom. In this article, the researcher presents a 5E-flipped learning environment approach and collected results of such data. The approach incorporates a 5E learning cycle model and flipped learning practices, making it accessible to anyone who wants to implement a 5E-flipped learning environment experience in their course. The 5E-flipped learning environment educational model proposes could help students to achieve higher order and deeper levels of learning as they engage in active work during online and face-to-face sessions. However, the thematic analysis of qualitative data three sources, participants learning dairy, focused group discussion and interview of 12 medical assistant students emerged some challenges they faced in a 5E-flipped learning environment. They faced challenges on learning activities which focused on fail to accomplish learning task and challenges on personal barriers related to lack of independent initiative and heavy responsibility on learners which influence their engagement in learning process. Therefore, the 5E-flipped learning activities need to be designed with these considerations in mind to encourage active student participation in online and classroom activities.